Peningkatan Self Confidence Dalam Ruang Lingkup Pendidikan Formal Melalui Program Storytelling Di Upt Sdn 066049 Medan Bersama Mahasiswi Kesejahteraan Sosial Fisip Usu - R A Roro Galuh Wigati (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Self confidence is an attitude that every student really needs to have. Because with self-confidence students will easily express ideas in their minds in learning. Students with less self-confidence will be hampered in achieving their achievements. Practitioners are interested in doing the second Field Work Practice in grades IV and V at UPT SDN 066049. Based on observations made by practicioners in grades IV and V, many of them lack confidence in learning. Lack of self-confidence makes many of them unable to get maximum results in learning. The practice in this study used the groupwork method and used a descriptive qualitative approach with a case study approach. The implementation of the Field Work Practice activities was carried out for approximately four months to see whether the objectives of the program were achieved. It is hoped that students in grades IV and V at UPT SDN 066049 can have high self-confidence so that students have high enthusiasm in completing what is the target of their learning.